How can studying the Arctic help us predict future European climate beyond the mean? (Policy briefing booklet) - Olsen, Steffen; Swingedouw, Didier; Langehaug, Helene; Ballester, Joan; Grist, Hannah (Zenodo, 2020)
This is a booklet on Tipping points, extreme events and uncertainty. The contents of this booklet have been presented at the policy briefing held at the European Parliament on 14 October 2020. The full set of presentations is available here: https://www.zenodo.org/record/4106029 : The Blue-Action project has received funding from the European Union's Horizon 2020 Research and Innovation Programme under Grant Agreement No 727852.